Effects of photobiomodulation combined with rehabilitation exercise on pain, physical function, and radiographic changes in mild to moderate knee osteoarthritis: A randomized controlled trial protocol - Yan Ling Tay; Mohd Azzuan Ahmad; Nor Hamdan Mohamad Yahaya; Devinder Kaur Ajit Singh (PLoS ONE, 2025)
Background Photobiomodulation, specifically high-energy photobiomodulation therapy (H-PBMT), is gaining recognition as a promising non-invasive intervention for managing knee osteoarthritis (KOA). While H-PBMT has demonstrated effectiveness in reducing pain and improving physical function, most evidence to date focuses on short-term symptomatic relief. The potential for H-PBMT to offer sustained benefits and modify the underlying progression of KOA remains insufficiently explored, warranting further investigation. Objective This study aims to assess the short-term and sustained effects of H-PBMT combined with rehabilitation exercises in patients with mild to moderate KOA, focusing on knee radiographic morphological changes over a 3-month follow-up period. Methods This protocol outlines a parallel-group, randomized, double-blind, placebo-controlled trial. Fifty participants with mild to moderate KOA (based on the Kellgren-Lawrence classification) will be randomly assigned to either the active H-PBMT plus exercise group (H-PBMT+E, n = 25) or the placebo photobiomodulation plus exercise group (PL+E, n = 25). Both groups will undergo an 8-week intervention, consisting of conventional rehabilitation exercises paired with either active or placebo photobiomodulation. H-PBMT will be delivered using the BTL-6000 HIL device with a 1064 nm wavelength, providing a total energy dose of 3190 J per 15-minute session. The treatment protocol includes both pulse mode (25 Hz, 5 W, 190 J) for analgesia and continuous mode (5 W, 3000 J) for biostimulation. Participants will be blinded to their group allocation through the use of a placebo device that mimics the active treatment without emitting therapeutic energy. Additionally, the outcome assessors will be blinded to the group allocations to ensure unbiased evaluation of the trial outcomes. The primary outcome is the Knee Injury and Osteoarthritis Outcome Score. Secondary outcomes include the Timed Up-and-Go test, Numerical Pain Rating Scale, and knee X-rays. Outcomes will be evaluated at baseline, immediately post-intervention (week 8), and at 3-month follow-up (week 20). Data will be analyzed according to the intention-to-treat principle, with a two-way repeated measures ANOVA used to assess time, group, and interaction effects. Conclusion This study is expected to provide valuable insights into the sustained effects and potential disease-modifying properties of combining H-PBMT with rehabilitation exercises in managing KOA. The findings could inform more effective treatment protocols, improving rehabilitation outcomes and patient quality of life. Trial registration Australian New Zealand Clinical Trials Registry (ACTRN12624000699561p).